Static Solutions of Mixed Burgers-KdV Equation I (Journal of Partial Differential Equations, 1988)
We show that, for given positive parameters &#946 and y, the Burgers-KdV equation. (1.5) has infinitely many static solutions satisfying given boundary conditions (2.1) or (3.3), and that these solutions differ from each other mainly by their numbers of extremum points.